Transfert de masse non-stationnaire depuis des particules sous écoulement - Bielinski, Clément; Kaoui, Badr (Comptes Rendus. Mécanique)
Mass transfer from particles is encountered in many biomedical applications. In operating conditions, particles are subjected to flows whose effect on solute transport is still not well understood. In this article we consider mass transfer from core-shell capsules and fibers subjected to various flow conditions. The combined effects of the flow and the shell permeability on the mass transfer efficiency are analyzed and quantified by correlations for the Sherwood number (the dimensionless mass transfer coefficient). The permeability is found to significantly affect the mass transfer efficiency, but it is a hardly measurable quantity. A new characterization method is proposed and validated using experimental data. All the obtained results can be applied to heat transfer from or to particles subjected to flow.